Explore the association of sports consumer behaviour and the structure of sports management - JIA PENGJU, JIA PENGJU; DR. ABHIJIT GHOSH, DR. ABHIJIT GHOSH (International Journal of Multidisciplinary Research and Studies, 2024)
Abstract Although sports organisations have made huge sums of money off of the popularity of spectator sports over the past three decades, the industry as a whole has recently seen significant shifts. According to Howard and Crompton, modern sports organisations must deal with rising costs, a saturated market, an economic disconnect, and the introduction of new technology (2005). The cost of running a sports organisation has skyrocketed in recent years, greatly outpacing the increase in income. The average salary in the NBA is more than 4 million per year, and a new NFL stadium may set you back more than 1 billion. The typical price tag for a Division IA programme is well over 20 million. Spectator dollars are a hot commodity, and the race to win them has never been fiercer. In the United States and Canada, sports fans may choose from more than 600 professional teams and 1,000 collegiate sporting programmes. In addition, as ticket costs continue to rise, many middle- and lower-class Americans are feeling alienated from the teams they formerly supported because of financial constraints. The advent of new technology presents both opportunities and threats to sports organizations.